Utility of routine viral load, CD4 cell count, and clinical monitoring among adults with HIV receiving antiretroviral therapy in Uganda: randomised trial. (9th November 2011) - Mermin, Jonathan; Ekwaru, John P; Were, Willy; Degerman, Richard; Bunnell, Rebecca; Kaharuza, Frank; Downing, Robert; Coutinho, Alex; Solberg, Peter; Alexander, Lorraine N; Tappero, Jordan; Campbell, James; et al.
Abstract : Objective To evaluate the use of routine laboratory monitoring in terms of clinical outcomes among patients receiving antiretroviral therapy (ART) in Uganda. Design Randomised clinical trial Setting A home based ART programme in rural Uganda. Participants All participants were people with HIV who were members of the AIDS Support Organisation. Participants had CD4 cell counts <250 cells × 10 6 /L or World Health Organization stage 3 or 4 disease. Interventions Participants were randomised to one of three different monitoring arms: a viral load arm (clinical monitoring, quarterly CD4 counts, and viral load measurements), CD4 arm (clinical monitoring and CD4 counts), or clinical arm (clinical monitoring alone). Main outcome measures Serious morbidity (newly diagnosed AIDS defining illness) and mortality. Results 1094 participants started ART; median CD4 count at baseline was 129 cells × 10 6 /L. Median follow-up was three years. In total, 126 participants died (12%), 148 (14%) experienced new AIDS defining illnesses, and 61(6%) experienced virological failure, defined as two consecutive viral loads >500 copies/mL occurring more than three months after the start of ART. After adjustment for age, sex, baseline CD4 count, viral load, and body mass index, the rate of new AIDS defining events or death was higher in the clinical arm than the viral load arm (adjusted hazard ratio 1.83, P=0.002) or the CD4 arm (1.49, P=0.032). There was no significant difference between the CD4 arm and the viral load arm (1.23, P=0.31). Conclusion In patients receiving ART for HIV infection in Uganda, routine laboratory monitoring is associated with improved health and survival compared with clinical monitoring alone. Trial registration Clinical Trials NCT00119093 .